Positive psychological resources, management responsiveness and psychological contract violation: A mediating effect of psychological contract breach - Eh Wen, Nen Di (2015)
Most researches on emotion, especially psychological contract violations are viewed from the exogenous constructs lenses i.e. the outcomes of violation which were generally displayed via attitudinal and behavioral evidences. In contrast, this study aims to discuss psychological contract violation from the opposite direction, i.e. the endogenous construct viewpoint. Using PLS-SEM, the five exogenous constructs i.e. the management of responsiveness, efficacy, hope, resiliency and optimism were posited as predictors of the psychological contract violation. Psychological contract breach, on the other hand was inserted as the mediator. The validity of this model was tested using 251 samples from individual responses of the SMBA member companies. The management of responsiveness, efficacy, hope and resiliency were found to be significant predictors for psychological contract violation. In contrary, optimism construct showed no evidence of relationship with the violation. The Psychological contract breach meanwhile was found to partially mediate the relationship of the management of responsiveness and the psychological contract violation. Other exogenous constructs have no direct relationship with the psychological contract breach; therefore the role of psychological contract breach as the mediator does not exist. The originality and contribution of this research was primarily the application of exogenous constructs which were uncommonly used as psychological contract violation predictor. Other implications, limitations and future research opportunities on the subject of psychological contract violation were also discussed